Low Class Primary School Students' Handwriting Readability Using Behaviorism Theory - Ade Eka Anggraini; Radeni Sukma; Oktaviani Adhi Suciptaningsih; Mardhatillah; Moh. Rozy Zamroni; Okta Mela Cikal Santoso; May Yati (Postgraduate, University of Mataram, 2024)
Handwriting is a typical work result expressed in the form of letters, symbols and numbers. This research uses qualitative research methods with a case study design. The aim of the research was to determine the legibility of class 1 students' handwriting. The data collection instruments used were in-depth interviews, observation and document study. Researchers validated the data by triangulating data collection techniques and triangulating data sources. The results of the research are that behaviorism theory provides an understanding of how the legibility of lower grade elementary school students' handwriting develops through learning, experience and reinforcement. However, other factors also need to be considered in understanding the legibility of students' handwriting.